Gestión del talento humano y su incidencia en el desempeño laboral del personal de la Cooperativa Ahorro y Crédito Nuestra Señora del Rosario Ltda. N° 222-Huamachuco: 2015. - Cruz Romero, Magaly Janett (2015)
The present work of investigation was elaborated by the purpose of proposing a Model of resource management Human beings and the productivity of personnel of the company Cooperativa Ahorro y Crédito nuestra Señora del Rosario Ltda. N°222 Huamachuco: 2015. With the determination of this work, the company will put emphasis in the most relevant points at which not they being employed correctly, allowing a performance adapted inside the organization For the present research report the design was in use descriptive - transeccional, statistician; and a survey was applied as technology of investigation. In the surveys applied to the personnel of the company Cooperativa Ahorro y Crédito nuestra Señora del Rosario Ltda. N°222 Huamachuco: 2015, we Can highlight that a Model of Resource management human beings allows to increase in a significant way the productivity of the Personnel of the company Cooperativa Ahorro y Crédito Nuestra Señora del Rosario. Since conclusion of the same one The management human talent affects in a direct way in the labor performance, devoting showing itself in the dissatisfaction of the workers for knowing each and every of the administrative processes developed inside the institution and the elements that intervene in them, both personnel and material.